2022
DOI: 10.1002/cb.2021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smartphone assistants' anthropomorphism on consumers' psychological ownership and perceived competence of smartphone assistants

Abstract: Few studies on the effects of smartphone assistants' anthropomorphism on consumer behavior have been conducted. This study explored the effects of anthropomorphism on consumers' psychological ownership of smartphone assistants and perceptions of their competence. Moreover, it investigated arousal during smartphone assistant use and examined how relationship norms governing the consumer–smartphone assistant relationship moderate the effects of anthropomorphism on psychological ownership. In study 1, which had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…The attribution of human features, motivations, and behaviors to inanimate objects is known as anthropomorphism (Aggarwal & McGill, 2007; Cheng, 2022; Herak et al, 2020; Ketron & Naletelich, 2019). Studies have reported humans frequently interact with and responded to computers in social manners despite acknowledging computers are not humans (Moon, 2000; Nass et al, 1997; Nass & Moon, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The attribution of human features, motivations, and behaviors to inanimate objects is known as anthropomorphism (Aggarwal & McGill, 2007; Cheng, 2022; Herak et al, 2020; Ketron & Naletelich, 2019). Studies have reported humans frequently interact with and responded to computers in social manners despite acknowledging computers are not humans (Moon, 2000; Nass et al, 1997; Nass & Moon, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…van Doorn et al ., 2017). Anthropomorphism refers to the individuals' cognitive process of assigning unique human attributes and characteristics, especially physical appearance or physical reactions, to non-human agents (Abdi et al ., 2022; Cheng, 2022; Epley et al ., 2007). In this sense, AI-based intellectual intelligence can be understood as a replica of human intelligence, as it reflects humans' cognitive intelligence (Siau and Yang, 2017), making HSRs more human-like (Lv et al.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, digital companions are considered more as friends who accompany users on their customer journey. This characterization is likely to evoke a communal relationship norm, where consumers perceive the agent more as a social entity that cares about them and with whom they wish to build a relationship (Cheng, 2022; Clark & Mills, 1979). To build such a relationship, a proposed match between the digital entity and the customer may not be sufficient, but require additional components (Pentina et al, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Specifically, we argue that this match frame is likely to induce goal‐relevant similarity perceptions only when the virtual counterpart is felt as humanlike. Only such an anthropomorphized entity is perceived as being able to experience emotions, understand human needs, and build a communal relationship (Cheng, 2022; Epley et al, 2007; Zhang et al, 2022). Yet, humanlikeness by itself is not sufficient to induce similarity perceptions either because an anthropomorphized face, voice, and body movement alone does not necessarily evoke the perception of sharing consumption goal‐relevant characteristics with the companion.…”
Section: Hypotheses Developmentmentioning
confidence: 99%